2001
DOI: 10.1002/ijc.1212
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of sensitivity to capecitabine in human renal carcinoma cells transfected with thymidine phosphorylase cDNA

Abstract: The purpose of the present study was to examine directly the role of thymidine phosphorylase (TP) in the sensitivity of renal cell carcinoma (RCC) to a novel fluoropyrimidine carbamate, capecitabine. TP cDNA-transfected RCC are used in these experiments to provide a basis for improved therapeutic benefit in chemoimmunotherapy. Human RCC line KU2 cells were transfected with pcDNA3.1/zeo(؉) with or without human TP cDNA by the lipofectin method. We established a clone transfected with pcDNA3.1/zeo(؉)/TP (KU2-TP1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
0
18
0
1
Order By: Relevance
“…Many basic and clinical studies have indicated that 5-FU-contaning regimens are more effective for TP-overexpressing tumour cells as compared with TP-less-expressing tumour cells (Fox et al, 1997;Evrard et al, 1999;Gasparini et al, 1999;Morita et al, 2001;Yang et al, 2002). Therefore, these two scenarios should be further studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many basic and clinical studies have indicated that 5-FU-contaning regimens are more effective for TP-overexpressing tumour cells as compared with TP-less-expressing tumour cells (Fox et al, 1997;Evrard et al, 1999;Gasparini et al, 1999;Morita et al, 2001;Yang et al, 2002). Therefore, these two scenarios should be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies showed that 5 0 -DFUR is much more active in TP-transfected cells than in mocktransfected cells (Patterson et al, 1995;Evrard et al, 1999). It is also true that 5 0 -DFUR is more effective for TP-overexpressing tumour xenografts than for tumour xenografts expressing normal or low levels of TP (Morita et al, 2001;Ishikawa et al, 1998). Furthermore, several preliminary studies also confirmed that TP expression in tumour cells was a predictive factor for favourable prognosis in cancer patients treated with 5 0 -DFUR (Yamamoto et al, 1996;Ishii et al, 1996;Koizumi et al, 1999;Nishimura et al, 2002).…”
mentioning
confidence: 99%
“…We previously transfected TP cDNA into the human renal cancer cell line KU2 to examine its sensitivity to fluoropyrimidines, and showed that transfection of TP cDNA made the cells sensitive to 5′DFUR and capecitabine [36]. Our previous study suggests that capecitabine exerts an antitumor effect primarily on cells with high TP expression.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies with the transfection of TP cDNA into various cancer cell lines showed that TP plays an important role in the activation of 5′DFUR [35]and capecitabine [36]. We previously transfected TP cDNA into the human renal cancer cell line KU2 to examine its sensitivity to fluoropyrimidines, and showed that transfection of TP cDNA made the cells sensitive to 5′DFUR and capecitabine [36].…”
Section: Discussionmentioning
confidence: 99%
“…A clear correlation was found between TP activity and in vitro sensitivity to the 5-FU analogue 5 0 -dFUR, and to a lesser extent to 5-FU itself. [76][77][78][79][80][81] Marchetti et al 76 also studied the effect of TP overexpression on in vivo tumour growth in a rat model. The impact on tumour growth turned out to be relatively modest and only involved the initial stages of tumour growth.…”
Section: -Fluorouracilmentioning
confidence: 99%